Heart rate variability biofeedback training protocol for measure discipline and responsibility among student - Hamzah, Shahidah; Johar, Siti Sarawati; Md Nor, Noranifitri; Yusoff, Nur Hafizah; Ani, Fauziah; Tahir, Zurinah (Science Press, 2020)
This paper describes an eight steps of heart rate variability (HRV) biofeedback protocol we have used in this research. In this step have three activities and four recovery time. This protocol was refined in a study of biofeedback to measure discipline and responsibility among student. These methods have been used for various therapy such as anxiety, depression and other psychophysiological disorders. The aim of biofeedback is to measure and improve the conscious control of individual’s involuntary physiological activity. Research has shown that this biofeedback protocol can measure stage of discipline and responsibility among student.